2010
DOI: 10.1002/ajim.20824
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous task recognition among U.S. adolescents working in the retail or service industry

Abstract: Working adolescents appear to underestimate the dangers associated with work, thus increasing the potential likelihood of injury. Emphasis should be placed on eliminating or reducing hazards in the workplace while simultaneously improving young workers' recognition of the hazardous nature of many of the tasks they perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Previous research has identified several areas that could contribute to the high rate of injuries among young workers, including a lack of experience, an underestimation of risk, and the lack of fully developed cognitive control systems. [12][13][14] However, additional analyses including task and occupational variables are needed to determine if the high injury rates for young workers are related to high-risk tasks or other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has identified several areas that could contribute to the high rate of injuries among young workers, including a lack of experience, an underestimation of risk, and the lack of fully developed cognitive control systems. [12][13][14] However, additional analyses including task and occupational variables are needed to determine if the high injury rates for young workers are related to high-risk tasks or other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-one percent of the inhalation-related injuries in the services industries were incurred by women (26,800; 95% CI: 16,300-37,500) in comparison to men (17,000; 95% CI: 10,600-23,400). Within services, 84% (13,200; 95% CI: 7800-18,600) of the injuries in the health care and social assistance sector were to women. Whereas, within public administration industries 84% (13,600; 95% CI: 9500-17,700) of the injuries were to men.…”
Section: The Distribution Of Work-related Nonfatal Inhalation Injurie...mentioning
confidence: 99%
“…The study by Runyan et al 35 of adolescent workers in the retail and service sector found that only a small proportion of respondents who reported hazardous exposures indicated that they used PPE. Vladutiu et al 36 reported that among adolescent workers who performed tasks known to be hazardous, very few actually recognised these tasks as being hazardous or dangerous. Findings from these studies suggest that (1) adolescent workers may not recognise hazardous work conditions and (2) they may be less likely to use PPE even when they are aware of hazardous exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Youth may not be physically able to safely operate certain machinery and equipment at work [Chang et al 2010;Fathallah et al 2009], and employer-supplied personal protective equipment (e.g., safety glasses, gloves, hardhats) may not adequately protect youth due to fit issues. Further, youth, especially those at the younger end of the spectrum (i.e., less than 16 years), do not have fully developed cognitive control systems [Steinberg 2008] and are more likely to underestimate the dangers associated with work [Vladutiu et al 2010].…”
Section: Introductionmentioning
confidence: 99%